Pluripotent Core in Bovine Embryos: A Review - Aguila, Luis (2022)
Early development in mammals is characterized by the ability of each cell to produce a complete organism plus the extraembryonic, or placental, cells, defined as pluripotency. During subsequent development, pluripotency is lost, and cells begin to differentiate to a particular cell fate. This review summarizes the current knowledge of pluripotency features of bovine embryos cultured in vitro, focusing on the core of pluripotency genes (OCT4, NANOG, SOX2, and CDX2), and main chemical strategies for controlling pluripotent networks during early development. Finally, we discuss the applicability of manipulating pluripotency during the morula to blastocyst transition in cattle species.